Bioactive injectable polymethylmethacrylate/silicate bioceramic hybrid cements for percutaneous vertebroplasty and kyphoplasty. (August 2019) - Sun, Xin; Wu, Zhi; He, Dan; Shen, Kangping; Liu, Xingzhen; Li, Haiyan; Jin, Wenjie
Abstract: Polymethylmethacrylate (PMMA) cement has been widely used to fill and stabilize hard tissue defects in clinical surgery, especially in percutaneous vertebroplasty (PVP) and percutaneous kyphoplasty (PKP). However, the dense body of pure PMMA in defects has no ability to promote bone regeneration. We herein aim to fabricate novel PMMA/silicate bioceramic hybrid cements by adding bioactive calcium silicate (CS) particles into PMMA to endow PMMA/CS hybrid cements with bioactivity and biodegradability without losing the excellent mechanical strength and injectability. Following comprehensive characterization of the physicochemical properties and in vitro bioactivity study, our results showed compared with PMMA cement, the constructed PMMA/CS hybrid cements possessed significantly lower curing temperatures and simultaneously retained the acceptable mechanical strength and injectability. Moreover, obvious bioactive ion release and hydroxyapatite formation could be detected and observed after the PMMA/CS hybrid cements were soaked in simulated body fluid, indicating their pronounced bioactivity. A further in vivo study of the PMMA/CS hybrid cements on goat vertebral body defect models reflected that the PMMA/CS hybrid cements could be biodegraded well and could significantly promote new bone formation in defects 6 months of post-injection. Our results suggest that PMMA/CS hybrid cements may be promising candidates for PVP and PKP in clinic. Graphical abstract: Image 1